2015
DOI: 10.3171/2015.2.spine14970
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of the Chêneau brace on coronal and sagittal alignment in adolescent idiopathic scoliosis

Abstract: OBJECT The aim of the present study was to retrospectively evaluate progressive correction of coronal and sagittal alignment and pelvic parameters in patients treated with a Chêneau brace. METHODS Thirty-two patients with adolescent idiopathic scoliosis (AIS) were assessed before initiation of bracing treatment and at the final follow-up. Each patient underwent radiological examinations, and coronal, sag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 18 publications
5
42
0
1
Order By: Relevance
“…Today there are numerous studies on brace treatment of patients with AIS [18][19][20][21][22][23][24] . In the US, UK, Scandinavia and some countries in Asia, the Boston brace is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Today there are numerous studies on brace treatment of patients with AIS [18][19][20][21][22][23][24] . In the US, UK, Scandinavia and some countries in Asia, the Boston brace is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is also an important goal to restore the sagittal balance in the AIS patients. However, Fang et al [23] found bracing did not significantly improve sagittal Cobb's angle, although increased it in some patients. Accordingly, we proposed it might not be enough to give brace treatment for a patient with smaller sagittal Cobb's angle of the thoracic curve, which seemed to be in consistent with the conclusion of Yu et al [14] …”
Section: Discussionmentioning
confidence: 96%
“…Symmetrical braces (Boston style with dorsal or ventral closures) provide success rates of 70% or little over [7,9,[32][33][34][35] (Figure 2). Asymmetrical threedimensional braces (mainly Chêneau style) may have success rates between less than 50 and more than 90% [8,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]. There is a wide variety of outcomes used in research, which may be related to the differing qualities of asymmetrical brace adjustments and designs (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…Brace treatment is supported by high-quality evidence as well [7][8][9]; however, the approach to bracing differs significantly in design (Figure 1). There are many types such as symmetrical braces [7,9,[32][33][34][35], asymmetrical braces [8,[36][37][38][39][40][41][42][43][44][45][46][47][48][49], night-time braces [50][51][52][53][54][55] and soft braces [56,57]. It has been shown that soft braces have no advantage over hard braces [8,[58][59][60].…”
Section: Introductionmentioning
confidence: 99%